The Regulatory Role of RNA Metabolism Regulator TDP-43 in Human Cancer - Ma, Xueyou; Ying, Yufan; Xie, Haiyun; Liu, Xiaoyan; Wang, Xiao; Li, Jiangfeng (Frontiers in Oncology, 2021)
TAR-DNA-binding protein-43 (TDP-43) is a member of hnRNP family and acts as both RNA and DNA binding regulator mediating RNA metabolism and transcription regulation in various diseases. Currently, emerging evidence gradually elucidates the crucial role of TDP-43 in human cancers like it’s previously widely researched in neurodegeneration diseases. A series of RNA metabolism events including mRNA alternative splicing, transport, stability, miRNA processing, and ncRNAs regulation are all confirmed to be closely involved in various carcinogenesis and tumor progressions, which are all partially regulated and interacted by TDP-43. Herein, we conducted the first overall review about TDP-43 and cancers to systematically summarize the function and precise mechanism of TDP-43 in different human cancers. We hope it would provide basic knowledge and concepts for tumor target therapy and biomarker diagnosis in the future.